ANALISIS EKUITAS MEREK KOMUNIKASI PEMASARAN TERPADU PADA MODA OJEK ONLINE ‘’GRAB’’ - DWI MUHAMMAD TAQWA; HARDYANSYAH (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The purpose of this research are to: 1. To study and analyze the Brand Equity of Grab online ojek equity in Palembang, 2. To study and analyze the Integrated Marketing Communication of IMC Ojek Grab Online in Palembang. "Qualitative research methods are types of research that produce findings that cannot be achieved using statistical procedures or other ways of quantification. Qualitative research can be used for research on community life, history, behavior , organizational functionalization, social activities, etc. The results of the study can conclude that the IMC is carried out by fulfilling the requirements and results of Brand Equity that gives trust, and loyalty to users.